Development of science learning media-based local wisdom Batui to improve critical thinking ability - Supandi, Muliati; Senam, Senam (Jurnal Pendidikan dan Pengajaran, 2019)
The aim of this study was to develop product in the form of a Tumpe Ritual Game for Class VII junior high school students. The research used the research and developement (R & D) method developed by Thiagarajan. The research refers to the 4D model: define, design, develop and disseminate. The result of the study indicates that learning media developed is valid or meet the eligibility criteria. The feasibility category obtained from media experts and also the teacher is highly valid. The implementation of learning media in the classroom can increase students' active participation so that it has an impact on improving critical thinking skill. Gain scores obtained at the pre-test and post-test in the experimental class showed significant differences. TheÂ  gain score of experimental class was 0.67 and the control class was 0.54 with the medium category. The effectiveness of learning was done by Manova test with the acquisition of sig values. amounting to 0,000 (<0.05). These condition indicated that the media developed was valid, practical and effective to be used in the process of learning science in class VII SMP.